Self-Reported Usage, Functional Benefit, and Audiologic Characteristics of Cochlear Implant Patients Who Use a Contralateral Hearing Aid - Neuman, Arlene C. (Trends Hear, 2017)
Ninety-four unilateral CI patients with bimodal listening experience (CI plus HA in contralateral ear) completed a questionnaire that focused on attitudes toward hearing aid use postimplantation, patterns of usage, and perceived bimodal benefits in daily life. Eighty participants continued HA use and 14 discontinued HA use at the time of the questionnaire. Participant responses provided useful information for counseling patients both before and after implantation. The majority of continuing bimodal (CI plus HA) participants reported adapting to using both devices within 3 months and also reported that they heard better bimodally in quiet, noisy, and reverberant conditions. They also perceived benefits including improved sound quality, better music enjoyment, and sometimes a perceived sense of acoustic balance. Those who discontinued HA use found either that using the HA did not provide additional benefit over the CI alone or that using the HA degraded the signal from the CI. Because there was considerable overlap in the audiograms and in speech recognition performance in the unimplanted ear between the two groups, we recommend that unilateral CI recipients are counseled to continue to use the HA in the contralateral ear postimplantation in order to determine whether or not they receive functional or perceived benefit from using both devices together.